First results from CSSWE CubeSat: Characteristics of relativistic electrons in the near‐Earth environment during the October 2012 magnetic storms. Issue 10 (31st October 2013) - Li, X.; Schiller, Q.; Blum, L.; Califf, S.; Zhao, H.; Tu, W.; Turner, D. L.; Gerhardt, D.; Palo, S.; Kanekal, S.; Baker, D. N.; Fennell, J.; et al.
Abstract [1] Measurements from the Relativistic Electron and Proton Telescope integrated little experiment (REPTile) on board the Colorado Student Space Weather Experiment (CSSWE) CubeSat mission, which was launched into a highly inclined (65°) low Earth orbit, are analyzed along with measurements from the Relativistic Electron and Proton Telescope (REPT) and the Magnetic Electron Ion Spectrometer (MagEIS) instruments aboard the Van Allen Probes, which are in a low inclination (10°) geo‐transfer‐like orbit. Both REPT and MagEIS measure the full distribution of energetic electrons as they traverse the heart of the outer radiation belt. However, due to the small equatorial loss cone (only a few degrees), it is difficult for REPT and MagEIS to directly determine which electrons will precipitate into the atmosphere, a major radiation belt loss process. REPTile, a miniaturized version of REPT, measures the fraction of the total electron population that has small enough equatorial pitch angles to reach the altitude of CSSWE, 480 km × 780 km, thus measuring the precipitating population as well as the trapped and quasi‐trapped populations. These newly available measurements provide an unprecedented opportunity to investigate the source, loss, and energization processes that are responsible for the dynamic behavior of outer radiation belt electrons. The focus of this paper will be on the characteristics of relativistic electrons measured by REPTile during the October 2012 storms; also included are long‐term measurements from the Solar Anomalous and Magnetospheric Particle Explorer to put this study into context.